Storage diseases of onion under variable conditions (Progressive Agriculture, 2015)
Onion (Allium cepa L.) is an important and familiar spice as well as vegetable crop throughout the world. Storage rot due to various diseases caused by bulb rotting fungi is a major constrain for storing onion year-round in Bangladesh. The fungi associated with onion collected from different markets of Mymensingh, Naogaon and Sathkhira districts of Bangladesh were studied aiming to record the incidence of storage diseases as well as storage variability and conditions on disease incidence of onion. Disease incidence was recorded from storage of the retailers in two local varieties of onion,viz.,Taherpuri, Faridpuri and one Indian variety Pusa Red. Initially, infected onion bulbs were found maximum in Faridpuri and minimum amount was found in Pusa Red. Month-wise disease incidence showed that highest number of infected onion bulbs was found in Pusa Red and lowest number of infected bulbs was found in Taherpuri. Similarly highest disease incidence (%) was recorded in Pusa Red and lowest disease incidence (%) was recorded in Therpuri. Among the different markets average number of fungal infected bulbs was highest in the samples collected from Dhamoirhat bazaar of Naogaon district and lowest in the samples collected from Natun bazaar of Mymensingh district. Highest infected bulbs were found in onions stored in cold room (6°C) followed by Free floor and Bamboo basket. Lowest infected bulbs were found in onions stored in dried sands followed by net-bag and jute bag. Thus, the fungal diseases in storage are higher in large sized onion bulbs than indigenous small sized onions and in cold room (6°C) than net-bag or jute bag.Progressive Agriculture 26:45-50, 2015